2020
DOI: 10.3389/fgene.2020.00475
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Resistance to Fusarium solani and Associated Genomic Regions in Common Bean Diversity Panels

Abstract: Common bean (Phaseolus vulgaris L.) production worldwide is hampered by Fusarium root rot (FRR), which is caused by Fusarium solani. Screening for FRR resistance on a large scale is notoriously difficult and often yields inconsistent results due to variability within the environment and pathogen biology. A greenhouse screening assay was developed incorporating multiple isolates of F. solani to improve assay reproducibility. The Andean (ADP; n = 270) and Middle American (MDP; n = 280) Diversity Panels were scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 70 publications
1
34
0
Order By: Relevance
“…Oladzad et al (2019b) identified resistance to Rhizoctonia solani in both gene pools, with no similar resistance regions identified. Similarly, Zitnick-Anderson et al (2020) found no similarity in significant regions associated with resistance to Fusarium solani between the two gene pools. In contrast, the similarity of the associated locations of CBB resistance in this study suggests that a similar genetic factor or mechanism produces the phenotype in both the Andean and Middle American populations.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Oladzad et al (2019b) identified resistance to Rhizoctonia solani in both gene pools, with no similar resistance regions identified. Similarly, Zitnick-Anderson et al (2020) found no similarity in significant regions associated with resistance to Fusarium solani between the two gene pools. In contrast, the similarity of the associated locations of CBB resistance in this study suggests that a similar genetic factor or mechanism produces the phenotype in both the Andean and Middle American populations.…”
Section: Discussionmentioning
confidence: 88%
“…The combination of the sequencing and assembly of the P. vulgaris genome (Schmutz et al, 2014) and the availability of massively parallel sequencing enabled the use of genomewide association studies (GWAS) in dry bean using GBSgenerated SNP data (Cichy et al, 2015;Kamfwa et al, 2015;Moghaddam et al, 2016;Zuiderveen et al, 2016;Soltani et al, 2017;Oladzad et al, 2019a,b;Zitnick-Anderson et al, 2020). In dry bean, the Middle American and Andean diversity panels were established by individually selecting primarily cultivated genotypes from the two gene pools (Cichy et al, 2015;Moghaddam et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different data sets previously reported for other common bean root rot-related pathogens in the Andean Diversity Panel ADP were also used in this study. The ADP represents the genetic diversity of cultivated germplasm of the Andean genepool, containing landraces, breeding lines and varieties from public and private breeding programs (Cichy et al, 2015a,b;Kamfwa et al, 2015a;Tock et al, 2017;Oladzad et al, 2019;Zitnick-Anderson et al, 2020). The ADP was evaluated for Pythium ultimum (Pyth_UGA) and Fusarium cuneirostrum (Fus_UGA) under greenhouse conditions at the CIAT-Kawanda research station (Uganda) as described by Amongi et al (2020) and Onziga Dramadri et al (2020).…”
Section: Plant Materialsmentioning
confidence: 99%
“…The ADP was evaluated for Pythium ultimum (Pyth_UGA) and Fusarium cuneirostrum (Fus_UGA) under greenhouse conditions at the CIAT-Kawanda research station (Uganda) as described by Amongi et al (2020) and Onziga Dramadri et al (2020). This panel was also evaluated under greenhouse conditions for resistance to Rhizoctonia solani (Rhiz_USA) and Fusarium solani (Fus_USA) at North Dakota State University (United States) as described by Oladzad et al (2019) and Zitnick-Anderson et al (2020). In addition, we used the Angular Leaf Spot (ALS) datasets reported by Nay et al (2019).…”
Section: Plant Materialsmentioning
confidence: 99%